Tanggung Jawab Notaris Terhadap Akta Jual Beli Saham Dengan Surat Kuasa Mewakili Yang Tanggalnya Melampui Akta - Putri, Anak Agung Ayu Adinda; Kartika, I Gusti Ayu Putri (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p18, 2021)
A share sale and purchase deed made by a notary based on a power of attorney whose date exceeds the deed often results in legal consequences. To determine the legal consequences that arise, Normative research is used, a statutory approach, uses primary and secondary legal material sources, and uses document study techniques. The aim is to be able to discuss the problems that arise, namely what are the legal consequences arising from the sale and purchase of shares by a notary based on a power of attorney representing the date beyond the deed and what is the form of responsibility by the notary from the legal consequences arising from the making of a share sale and purchase deed based on a power of attorney represents whose date exceeds the deed. The conclusion is that the authentic form of the deed has lost its authenticity, the authority of the party in the deed is considered invalid and invalid.   Akta jual beli saham yang dibuat oleh Notaris berdasarkan surat kuasa yang tanggalnya melampui akta seringkali menimbulkan akibat hukum.  Penelitian ini menggunakan jenis penelitian Normatif, pendekatan undang-undang, menggunakan sumber bahan hukum primer dan sekunder, dan menggunakan teknik studi dokumen. Tujuannya adalah untuk mengetahui akibat hukum yang timbul dari akta jual beli saham oleh Notaris berdasarkan surat kuasa mewakili yang tanggalnya melampaui akta dan untuk mengetahui bentuk tanggung jawab oleh Notaris dari akibat hukum yang timbul karena pembuatan akta jual beli saham berdasarkan surat kuasa mewakili yang tanggalnya melampui akta. Kesimpulannya adalah bentuk akta otentik tersebut hilang otentisitasnya, kewenangan dari penghadap di dalam akta  dianggap tidak sah dan tidak berlaku.